Karbon ve aramid elyaf esaslı üç boyutlu dokuma kumaş takviyeli kompozitlerin balistik ve mekanik özelliklerinin incelenmesi - Durdu, Seval (My University, 2022)
Tarihin ilk dönemlerinden bugüne insanlık, kendini ve yaşadığı yeri savunmayı hedefleyen bulgular aramış ve bu doğrultuda sürekli yeni şeyleri geliştirmeyi hedeflemiştir. Zırh malzemelerinin, ateşleyici silahların ve hatta kompozit malzemelerin temelleri dahi bu doğrultuda atılmış ve günümüze dek ilerlemiştir. Üretim endüstrisinde ise metal olmayan kompozit malzemeler; çelik ve diğer metallerin yerine alternatif olarak kullanılmaya başlanmıştır. Bu tez ile ülkemizde çok önemli bir yeri olan ve kullanımı gittikçe artan kompozit malzemeler hakkında çalışma yürütülmüştür. Gelişmekte olan ve gelecekte çok daha önem kazanması öngörülen bu malzeme sınıfı hakkında geniş bir araştırma yapılarak önemli bilgilerin derlenmesi ve bir kaynak oluşturulması, ayrıca bu malzemeler hakkında diğer bilim insanlarının da faydalanacağı bir tez çalışması hedeflenmiştir. Günümüzde teknolojinin gelişmesi ile ortaya çıkan yüksek mukavemet ve elastikiyet özelliklerine sahip hafif kumaşların polimerlerle kombinasyonları, balistik panel ve zırh üretiminin temelini oluşturmaktadır. Ayrıca daha geniş bir malzeme seçimi ve üretim kolaylığı, onları mühendislik uygulamaları için ideal kılmaktadır. Askeri alanlar başta olmak üzere balistik alanında yapılan yatırım, akademik ve askeri çalışmalar bu konunun önemini ortaya koymaktadır. Bu tez çalışmasında karbon ve aramid fiberler dokuma tezgahında üç katmanlı olarak dokunmuştur. Dokuma kumaşlar 3 katmanlı olarak %100 karbon ve %100 aramid elyaflar şeklinde 4 farklı kombinasyonda tasarlanmıştır. Matris malzemesi olarak epoksi reçinesi seçilmiş ve 4 farklı kompozit malzeme tasarlanmıştır. Gerçekleştirilen dokuma tasarımlarına ait malzeme modelleri MSC/ Digimat yazılımı kullanılarak hesaplanmış ve gerekli malzeme karakterizasyonları belirlenmiştir. Elde edilen malzeme verileri ile tasarlanan kompozit yapılar Sonlu Elemanlar Simülasyonları gerçekleştirerek incelenmiştir. Sonuçlar, tasarlanan kompozit yapılar için karşılaştırmalı olarak değerlendirilmiştir.

From the first periods of history to the present, humanity has searched for findings aiming to defend itself and the place where you live, and in this direction, it has aimed to develop new things constantly. Armor materials, firearms, and perhaps even the foundations of composite materials were laid in this direction and progressed until today. Non-metal composite materials in the manufacturing industry; it has started to be used as an alternative to steel and other metals. With this thesis, a study has been carried out on composite materials, which have a very important place in our country and are increasingly used. It is aimed to compile important information and create a resource by conducting extensive research on this developing material class, which is expected to gain much more importance in the future and also to publish a study about these materials that other scientists will benefit from. Polymer composite materials have started to be used as alternatives in the manufacturing industry instead of steel and other metals. Polymers and polymer matrix composites are increasingly used due to their high strength and low density. Additionally, a wider selection of materials and ease of production make them ideal for engineering applications. Nowadays, polymer matrix composite armors are widely used as an armor material and the use of composite armor for ballistic purposes is becoming more and more widespread. The combination of lightweight fabrics with high resistance and elasticity, which has emerged with the development of technology nowadays, is the basis of ballistic panels and armor production. Additionally, a more comprehensive selection of materials and ease of production make them ideal for engineering applications. Investments made in the field of ballistics, especially in military fields, and academic and military studies reveal the importance of this claim. ix The 3-layer fiber fabrics used in this study were wovens. Woven fabrics are woven in 4 ways: 100% carbon fiber and 100% aramid fiber fabrics. Epoxy resin was chosen as the matrix material, and four different composite materials were designed. The material models of the realized weaving designs were calculated using MSC/ Digimat software, and the necessary material characterizations were determined. Composite structures designed with the obtained material data were examined by performing Finite Element Simulations. The results were evaluated comparatively for the designed composite structures.
Keywords: Aramid; Balistik; Ballistic; Composite materials; Fiber; Fiber Composite; Kompozit; Kompozit malzemeler; Mechanic properties; Mekanik özellikleri